THE USE OF BATTLESHIP GAME IN TEACHING YES/NO QUESTIONS IN SIMPLE PRESENT TENSE - Suryanto, .; Supardi, Iwan; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research are to investigate the effectiveness and the effect size of using Battleship game in teaching Yes/No questions in simple present tense to the seventh grade students of SMP Negeri 2 Semparuk in academic year 2014/2015.Â This research was conducted as a pre-experimental research and the sample was class VIID which consists of 39 students. The data were collected through pre-test and post-test by using objective test consisting of twenty five items and were analyzed by using t-test and Effect Size (ES) formulas. The findings show that the t-computation is 16.6 (> 2.042) or higher than the t-table value with the degree of freedom of 38 and Î± of 0.05, and the effect of treatment is 2.67 (> 1.00) or categorized as strong effect. It indicates that the use of Battleship game is effective in teaching Yes/No questions in simple present tense. Keywords: Battleship game, Yes/No questions Â Abstrak: Penelitian ini bertujuan untuk mengetahui keefektifitian and tingkat efektifitas dari penggunaan Battleship game dalam pengajaran Yes/No questions dalam simple present tense terhadap siswa kelas 7 SMP Negeri 2 Semparuk tahun ajaran 2014/2015. Penelitian ini dilakukan dengan metode pre-eksperimen dan sampel penelitian ini adalah kelas VIID yang terdiri atas 39 siswa. Data penelitian dikumpulkan melalui pre-test dan post-test dengan menggunakan tes objektif yang berjumlah dua puluh lima soal dan data tersebut dianalisis dengan menggunakan rumus t-test dan ES (tingkat efektifitas). Hasil penelitian menunjukkan bahwa hasil perhitungan t-test adalah 16.6 (> 2.042) atau lebih besar dibandingkan dengan nilai t tabel dengan degree of freedom sebesar 38 dan Î± sebesar 0.05, dan tingkat efektifitas adalah 2.67 (> 1.00) atau dikategorikan memiliki efek yang kuat. Hal ini menandakan bahwa penggunaan Battleship game efektif dalam pengajaran Yes/No questions dalam simple present tense. Kata kunci: Battleship game, Yes/No questions Â